Proceedings of the Eleventh International Symposium on Mining With Backfill 2014
DOI: 10.36487/acg_rep/1404_28_grabinsky
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of as-placed cemented paste backfill properties from three mines

Abstract: Over the last few years considerable attention has been paid to predicting the as-placed properties of cemented paste backfill (CPB) using laboratory techniques that load the sample in ways that are thought to reasonably simulate the effective stress paths experienced by the CPB during initial placement and subsequent curing while backfilling is ongoing. Most of these studies suggest that consolidation mechanisms prior to significant hydration-induced stiffness increases are responsible for denser CPB and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…For a spike of pressure of 4 kPa, a volume of 5.4 m 3 would have had to be added to the backfill to increase the backfill height by 0.2 m. This displaced volume agrees with the typical flush size of 6 m 3 . The increase in vertical pressure between 14:00 and 15:15 is explained by a 'lava' type flow as previously captured by Grabinsky et al (2014), as shown in Figure 5a. The paste was building up in an area of the stope that did not influence the instrument.…”
Section: Stope 321-865-1w Blksupporting
confidence: 69%
“…For a spike of pressure of 4 kPa, a volume of 5.4 m 3 would have had to be added to the backfill to increase the backfill height by 0.2 m. This displaced volume agrees with the typical flush size of 6 m 3 . The increase in vertical pressure between 14:00 and 15:15 is explained by a 'lava' type flow as previously captured by Grabinsky et al (2014), as shown in Figure 5a. The paste was building up in an area of the stope that did not influence the instrument.…”
Section: Stope 321-865-1w Blksupporting
confidence: 69%
“…Estimating plug strength requirements is such a case, where using c = 1 2 UCS would reduce the calculated strength (UCS) requirement by a factor of two. If the recently placed backfill remains close to saturated, as was determined from field tests by [21,22], then c = 1 4 UCS must be used. It is therefore recommended that the assumption c = 1 4 UCS continue to be used until it can be demonstrated that greater estimates of cohesion are warranted.…”
Section: Discussion: Application At Other Mine Sitesmentioning
confidence: 99%
“…Although others have considered CPB strength increases due to self-weight consolidation during deposition [16][17][18][19][20], the slow start to effective stress development (Figure 2) compared to material cohesion development (Figure 3) suggests minimum potential for self-weight consolidation and associated strength gain at the studied mines. Indeed, [21,22] show that the as-placed bulk properties at Williams, Kidd, and Cayeli mines are the same as the as-mixed properties, except that occluded air was mixed into the paste during deposition which had the effect of slightly increasing void ratio and decreasing degree of saturation. Similar results are reported by [13] at Casa Berardi where cores from the CPB plug had void ratios similar to the as-mixed design.…”
Section: Strength Development During Field Poursmentioning
confidence: 96%
See 1 more Smart Citation
“…The minimal change in void ratio, shown in Figure 2, is comparable to the difference observed between the void ratios of freshly prepared laboratory samples and the void ratios determined from in situ samples from the test stopes, given the same recipe. Furthermore, these in situ samples all had similar void ratios and did not show much relationship with change of depth (Grabinsky et al 2014). This indicates that there is a slight change in consolidation experienced between fresh paste and deposited paste, but that this change is not dependent on the amount of material above.…”
Section: Figure 2 Compression Curves For Cpb Recipes From Three Test mentioning
confidence: 92%